Hungarian Monitoring, 12 June 1990 . [Magyar rádiófigyelő], 1990. június 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International politics: - Russia also wants to break with Soviet Union - Elections in Bulgaria - Earthquake in Romania - Government crisis in Israel Domestic affairs: - Remembering Imre Nagy and his martyred colleagues - Belgian royal couple in Budapest - Gorbachev congratulates Gyula Horn on becoming the president of Hungarian Socialist Party -The Saint Stephen battleship found in Adriatic sea Külpolitika: - Oroszország is ki akar szakadni a szovjet államközösségből - Választások Bulgáriában - Földrengés Romániában - Kormányválság Izraelben Belpolitika: - Megemlékezés Nagy Imre és mártírtársai emlékére - Budapesten a belga királyi pár - Gorbacsov táviratban köszönti Horn Gyulát az MSZP elnökévé választása alkalmából - Az Adriai-tengerben megtalálják a Szent István csatahajót